Institutionalization of REDD+ MRV in Indonesia, Peru, and Tanzania: progress and implications - Ochieng, R.M.; Arts, B.; Brockhaus, Maria; Visseren-Hamakers, I.J. (Resilience Alliance, Inc., 2018)
Reducing emissions from deforestation and forest degradation in developing countries (REDD+) has opened up a new global discussion on forest monitoring and carbon accounting in developing countries. We analyze and compare the extent to which the concept of measurement, reporting, and verification (MRV) for REDD+ has become institutionalized in terms of new policy discourses, actors, resources, and rules in Indonesia, Peru, and Tanzania. To do so, we draw on discursive institutionalism and the policy arrangement approach. A qualitative scale that distinguishes between “shallow” institutionalization on the one end, and “deep” institutionalization on the other, is developed to structure the analysis and comparison. Results show that in all countries MRV has become institutionalized in new or revised aims, scope, and strategies for forest monitoring, and development of new agencies and mobilization of new actors and resources. New legislations to anchor forest monitoring in law and procedures to institutionalize the roles of the various agencies are being developed. Nevertheless, the extent to which MRV has been institutionalized varies across countries, with Indonesia experiencing “deep” institutionalization, Peru “shallow-intermediate” institutionalization, and Tanzania “intermediate-deep” institutionalization. We explore possible reasons for and consequences of differences in extent of institutionalization of MRV across countries.